PENGARUH CARA PEMBERIAN VAKSIN ND LIVE PADA BROILER TERHADAP TITER ANTIBODI, JUMLAH SEL DARAH MERAH DAN SEL DARAH PUTIH - Bayu Saputro; Purnama Edy Santosa; Tintin Kurtini (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study aims to ; (1) determine the effect of adminitrastion of vaccine against ND Live onbroiler antibody titers, the number of red blood cells and white blood cell count, (2) determineantibody titers, the number of red blood cells and white blood cells are the best in broiler chickens NDvaccineby giving different live . this study conducted in October 2012 in the experimental cage unitPT. Rama Jaya Lampung is located in the village in new dawn, distrct grand teak, southern Lampung.Chickens were used as much as one hundred male sex.This study used a completely randomized design consisting of four treatments (P1: eye drops,P2: nose drops, P3: oral drops, P4: syringe) with repead five timesResults of analysis of variance showed that the way ND Live vaccines in broiler old seven day notaffected significantly (P<0.05) antibody titers, the number of red blood cells and white blood cellscount broiler.